Concanavalin A induced orientation immobilization of Nuclease P1: The effect of lectin agglutination. (January 2018) - Huang, Jinsha; Zhuang, Wei; Wei, Ce; Mu, Liwen; Zhu, Jiahua; Zhu, Yudan; Wu, Jinglan; Chen, Yong; Ying, Hanjie
Graphical abstract: Highlights: Nuclease P1 is orientedly immobilized onto activated porous carriers. Sugar-lectin affinity is proved by XPS chemical bond(CN, CO) analysis. Loading capacity of Nuclease P1 is 4.02 mg/g wet Con A modified support. Stability, reusability, and substrate affinity are improved. Abstract: Orientation immobilization of enzymes has attracted intensive interest owing to the retainable specific activity and stability. Specially, glycoprotein immobilized onto Concanavalin A (Con A) modified carriers induces the orientation of the enzyme. However, the effects of the interface properties of carriers and enzymes are still not well understood yet. In this study, we synthesized the activated porous poly (styrene- divinylbenzene) resin carriers with 30 nm pore sizes and 72 m 2  g −1 specific surface areas and decorated with Con A. The resultant loading capacity of NP1 on Con A modified carriers was as high as 4.02 mg g −1 wet support as a result of strong affinity between the enzyme and Con A decorated on carriers. It was found that the acid resistance, thermal stability, reusability and degradation efficiency of the immobilized enzyme on Con A modified porous carriers were significantly improved. The reduction of Km from 18.40 ± 0.55 mg mL −1 to 17.19 ± 0.51 mg mL −1 illustrated the improved substrate affinity of HA-GA-ConA-NP1 . Moreover, Con A-affinity NP1 exhibited the best operational stability that only 7% of its initial activity was lost even after 9 batches repeated reaction. This work demonstrates that surface property manipulation of porous carriers and its derivatives has great potential in efficient biocatalytic systems.